Histone H1 promotes silencing of unintegrated HIV-1 DNA - Jiaqi Zhu; Gary Z. Wang; Hugo D. Pinto; Sean E. Healton; Laxmi N. Mishra; Arthur I. Skoultchi; Stephen P. Goff (Proceedings of the National Academy of Sciences, 2026)
In eukaryotic cells, genomic DNA is packaged into chromatin with nucleosomes formed by core histones H2A, H2B, H3, and H4, and further stabilized by the linker histone H1. During the early stages of retroviral infection, such as with murine leukemia virus (MLV) and human immunodeficiency virus type 1 (HIV-1), host core and H1 histones are rapidly deposited onto unintegrated viral DNAs upon nuclear entry. These unintegrated viral DNAs are transcriptionally silenced through histone posttranslational modifications (PTMs), including high levels of H3K9 trimethylation and low levels of H3 acetylation. Linker histone H1 is closely associated with chromatin compaction and histone PTMs, suggesting a potential role in regulating retroviral DNA fate. In this study, we demonstrate that simultaneous knockdown of four somatic H1 variants (H1.2, H1.3, H1.4, and H1.5) in K562 cells reverses the silencing of unintegrated HIV-1 DNA, resulting in increased viral expression. Notably, this effect was specific to HIV-1, as the same H1 depletion did not alter the silencing of MLV unintegrated DNA. Furthermore, inhibition of H3K9 methylation also relieved HIV-1 silencing, and H1 depletion reduced H3K9me3 deposition on HIV-1 unintegrated DNA. These findings indicate that H1 regulates HIV-1 unintegrated DNA expression by promoting H3K9me3 deposition, a mechanism that appears distinct from that of MLV.